POTENTIAL OF CHEMICAL ELICITORS TO ENHANCE PRODUCTION SECONDARY METABOLITES IN INDUCED CALLUS FROM HYOSCYAMUS NIGER LEAVES - Khalaf, M. A.; Taha, A. J.; Abed, A. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Hyoscyamus niger have the main pharmaceutical tropane alkaloids and glycosides in their tissues. The study aimed to enhance the biosynthesis of these compounds by tissue culture techniques. Callus cultures were established from leaf explants on MS medium. Three chemical salts were added separately in different concentrations to the culture medium to evaluate their effects on callus growth and content of pharmaceutical compounds. The results demonstrate that copper (Cu) and cadmium (Cd) decreased callus weights, while the aluminum (Al) did not exhibit any significant effects, compared to the control treatment. However, the HPLC assay proved that the chemical stress caused beneficial effects in promoting the production of alkaloid and glycoside compounds in callus cultures. Succinctly, the highest concentration of Cu (36 mg/L) caused a significant increasing in the content of hyoscyamine, scopolamine, and hyoscyammoside-A. Whereas, Al and Cd at low concentration (5 mg/L) produced the varying significant increasing in the substances of tropane alkaloids and glycosides, compared to the other treatments and the control. These finding concludes that application of chemical elicitation in certain concentrations offer advantageous visions for developing the conditions that related with biosynthesis of medicinal compounds in H. niger.